A case series describing the risk of periodontal disease in Marfan syndrome patients harboring a possible aortic aneurysm or dissection - Kouta Umezawa; Takako Kajiwara; Kyoko Ishii; Tatsuya Hasegawa; Shigeto Suzuki; Masato Nakano; Mayu Sawaguchi; Venkata Suresh Venkataiah; Yoshio Yahata; Koki Ito; Yoshikatsu Saiki; Masahiro Saito (BMC, 2022)
Abstract Background Marfan syndrome (MFS) is a systemic disorder of connective tissues caused by insufficient elastic fiber formation that leads to structural weakness and results in various tissue disorders, including cardiovascular and periodontal disease. Notably however, the risk of periodontal disease in MFS patients affected by an aortic aneurysm or dissection has not yet been clarified. Methods We investigated the periodontal condition in the following three groups: MFS patients diagnosed with an aortic aneurysm or dissection with a planned aortic surgery (MFS surgery), MFS patients who had already undergone aortic surgery (MFS post-surgery) and healthy control patients (Healthy). The periodontal condition of all of these patients was evaluated at their first visit, reassessed again at two-month after the first visit, and evaluated again at a six-month follow-up after the reassessment. Results A total of 14 participants, 3 MFS surgery patients, 4 MFS post-surgery patients and 7 healthy control volunteers were examined. Saliva examinations revealed no significant differences between any of the groups at the first visit, reassessment, or follow-up. Interestingly, the MFS surgery cases showed a higher BOP and PISA at the first visit and follow-up compared with the other groups. In contrast, the MFS surgery patients showed an improvement in their LVDd and EF values, both markers of cardiac function, at the reassessment and follow-up compared with the first visit. Conclusions MFS associated with an aortic aneurysm or dissection leads to a higher risk of periodontal disease, indicating the need for more frequent oral hygiene maintenance in these patients. In addition, MFS patients who undergo frequent professional cleaning of their teeth show a lower onset of cardiovascular disease, suggesting that professional oral hygiene in these cases contributes to a healthier condition.